Access to medicines and patient satisfaction in healthcare facilities: A cross-sectional study of a Peruvian population-based survey - Valeria Gianell Olivera-Molina; Juan Carlo Maita-Durand; J. Jhonnel Alarco (Medwave)
Introduction Shortage of medicines in Peruvian healthcare facilities is a significant public health issue that may affect patient satisfaction.